Transaction Fraud Buy and Sell Online Through Restitution as Criminal Addition in the Electronic Information and Transaction Law - Vicki Dwi Purnomo; Hartanto; rohidin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The ITE Law as a legal framework for law enforcement for every crime arising from electronic information and transactions does not cover victim protection in the form of compensation (refund). This research was conducted normatively. The legal issues discussed in this study are: First, what kind of legal protection do victims of online buying and selling scams have? The aims of this study are: First, to analyze forms relating to the protection of fraud victims in online transactions. Amendments to the ITE Law are needed to include restitution as an additional offense so that restitution is not only an option proposed but an obligation that must be fulfilled.